1997
DOI: 10.1258/1357633971931174
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with multispecialty interactive teleconsultations

Abstract: Satisfaction with teleconsulting was evaluated for 96 patients using the Kentucky TeleCare telemedicine network. Consultant specialties included psychiatry (41), dermatology (24), clinical nutrition (20), anaesthesia (3), infectious diseases (3), rheumatology (2), internal medicine (1), neurology (1) and paediatric pulmonology (1). The results indicated a high level of patient satisfaction, with a mean score of 6.8 (on a 7-point Likert scale with 1 = strongly disagree and 7 = strongly agree) for the question '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 1 publication
3
41
0
Order By: Relevance
“…Comparing reported satisfaction levels across studies in different specialties is difficult because of variation in research methodology, and the failure to report on important study details. Although a large number of studies in this review reported data from a range of specialties, 29,32,54,57,58,61,63,65,70,75,87,93,106 differences between groups in terms of reported satisfaction were generally not examined. Small sample size prohibits the analysis of satisfaction across subgroups in several of these multispecialty studies.…”
Section: Factors That Mediate Patient Satisfaction With Telemedicinementioning
confidence: 99%
“…Comparing reported satisfaction levels across studies in different specialties is difficult because of variation in research methodology, and the failure to report on important study details. Although a large number of studies in this review reported data from a range of specialties, 29,32,54,57,58,61,63,65,70,75,87,93,106 differences between groups in terms of reported satisfaction were generally not examined. Small sample size prohibits the analysis of satisfaction across subgroups in several of these multispecialty studies.…”
Section: Factors That Mediate Patient Satisfaction With Telemedicinementioning
confidence: 99%
“…Videoconferencing is becoming the primary technology being used for psychotherapy in Behavioral Telehealth programs (Baer, Cukor, Jenike, Leahy, O'Laughlen, & Coyle, 1995;Cukor, Baer, Willis, Leahy, O'Laughlen, Murphy, Withers, & Martin, 1998;Huston & Burton, 1997;Glueckauf et al, 1998;Jerome, 1986Jerome, , 1993Sampson, Kolodinsky, & Greeno, 1997;Troster, Paolo, Glatt, Hubble, & Koller, 1995). The positive effect of interactive video upon the offline therapeutic alliance has been demonstrated by a number of researchers (Baigent, Bond, Kalucy, Yellowlees, Ben-Torin, Kavanagh, & Lloyd, 1997;Ball, McLaren, Summerfield, Lipsedge, & Watson, 1995;Ghosh, McLaren, & Watson, 1997;Jerome, 1993;McLaren, Blunder, Lipsedge, & Summerfield, 1996;Montani, Billaud, Tyrell, & Fluchaire, 1997).…”
Section: Behavioral Telehealthmentioning
confidence: 99%
“…We used a modified version of the questionnaire developed by the Kentucky Telecare Network, 36 which is used to evaluate perceived quality of mental health services. We modified the questionnaire slightly to accommodate for the differences in the three treatment conditions.…”
Section: Methodsmentioning
confidence: 99%